Electronic assistive technology used by people with acquired brain injury in shared supported accommodation: Implications for occupational therapy. (February 2017) - Jamwal, Rebecca; Callaway, Libby; Ackerl, Jane; Farnworth, Louise; Winkler, Di
Introduction: People with severe acquired brain injury often require lifetime support, sometimes received from paid workers if living in shared supported accommodation. Electronic assistive technology may offer a less intrusive method of support that can enable autonomous participation and deliver cost savings. However, research on rates, barriers, and facilitators of electronic assistive technology uptake is lacking. This study aimed to identify electronic assistive technology types used by people with acquired brain injury living in shared supported accommodation, assess user satisfaction and psychosocial impact of electronic assistive technology, detail the impact of technology use on respondents' participation and support needs, and describe barriers and/or facilitators to electronic assistive technology uptake and ongoing use. Method: Participants were identified electronic assistive technology users with acquired brain injury living in shared supported accommodation in Australia ( N = 22). Mixed methods data were collected using semi-structured interviews and published measures of support need, electronic assistive technology satisfaction, and psychosocial impact. Results: Participants reported satisfaction with the devices they used, and positive psychosocial outcomes. Areas impacted by electronic assistive technology, key facilitators and barriers to electronic assistive technology use, and implications for occupational therapists working to deliver electronic assistive technology solutions were identified. Conclusion: Electronic assistive technology use by this group can positively influence both everyday functioning and participation. Skilled prescription and ongoing support services are necessary to maximise uptake and use.